Implementasi Sistem Alih Daya atau Outsourcing Dalam Mencapai Kesejahteraan Pekerja Indonesia Ditinjau Dari Undang-Undang Nomor 13 Tahun 2003 - Julyatika Fitriyaningrum (Indonesian State Law Review, 2019)
The purpose of this article is to examine the implementation of outsourcing systems in Indonesian labor law. In implementing this system there are differences, namely the implementation in the field and what is stated in the contents of the Act. So that in reality the implementation of labor law has not been able to create a harmonious relationship between workers or workers and employers and has not been able to improve the welfare of workers/laborers. Based on Article 66 of Law No. 13 of 2003 the implementation of the outsourcing system is only allowed if it does not involve the main activities (core business) or activities that are not directly related to the production process. These activities include cleaning service businesses, provision of food (catering), businesses of security personnel, the business of supporting services in mining and petroleum, as well as efforts to provide transportation for workers/laborers. The interpretation of outsourcing provided by the Act, in reality, is still very limited compared to the needs of the business world today. The rights that must be obtained by outsourcing employees are getting wages, overtime pay, getting leave rights, THR or holiday allowances, social security protection, and layoff compensation.